2016
DOI: 10.5604/20831862.1200511
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-session reliability of medial gastrocnemius architectural properties

Abstract: This study aimed to determine the within- and between-session reliability of medial gastrocnemius (MG) architecture (e.g. muscle thickness (MT), fascicle length (FL) and pennation angle (PA)), as derived via ultrasonography followed by manual digitization. A single rater recorded three ultrasound images of the relaxed MG muscle belly for both legs of 16 resistance trained males, who were positioned in a pronated position with their knees fully extended and the ankles in a neutral (e.g. 90°) position. A subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…As this cannot be done on single-image fascicle lengths, our results suggest that it is worthwhile to record image sequences with fascicle movement, even for studies interested in single-image analyses. SEM values between different raters remain rather high (4.15 and 4.29 mm for DIT and UFI respectively) for both strategies, especially compared to intra-rater SEM values (average of 2.59 ± 1.56 mm), but are within the range reported in other studies ( König et al, 2014 ; McMahon, Turner & Comfort, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As this cannot be done on single-image fascicle lengths, our results suggest that it is worthwhile to record image sequences with fascicle movement, even for studies interested in single-image analyses. SEM values between different raters remain rather high (4.15 and 4.29 mm for DIT and UFI respectively) for both strategies, especially compared to intra-rater SEM values (average of 2.59 ± 1.56 mm), but are within the range reported in other studies ( König et al, 2014 ; McMahon, Turner & Comfort, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…This has the potential to result in low reliability and low repeatability because of the subjective nature of this analysis. Studies on the reliability of fascicle identification from ultrasound images during a wide range of tasks, including measurements of muscle in a relaxed and contracted state, during walking, running and jumping, have reported standard error of measurement (SEM) percentages of 4.3–14.2% for inter-session ( Kwah et al, 2013 ), 0.0–8.3% for inter-image ( Kwah et al, 2013 ) and 3.8–7.5% for inter-rater ( König et al, 2014 ; McMahon, Turner & Comfort, 2016 ) analyses. Overall, these values remain rather high, considering the effect sizes generally reported in cross-sectional or longitudinal training studies (10–19%) ( Abe, Kumagai & Brechue, 2000 ; Fukutani & Kurihara, 2015 ; Timmins et al, 2016 ) and in studies that compare fascicle length changes between various conditions within similar dynamic tasks (9–14%) ( Lichtwark & Wilson, 2006 ; Farris & Sawicki, 2012 ; Brennan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a change in PA post-eccentric training might be due to measurement errors in US image analysis (Baroni et al, 2013b). While eccentric training and conventional resistance training seem to increase plantar flexor PA by around 1.2–4.0° (Morse et al, 2007; Duclay et al, 2009; Vieillevoye et al, 2010; Sanz-Lopez et al, 2016), ultrasonographic analyses have shown a TE of 0.15–3.7 (de Boer et al, 2008; Padhiar et al, 2008; Martins et al, 2012; McMahon et al, 2016). Reported PA adaptive responses to strength training are close to the measurement error in US analysis, which could explain results from studies that found an increase in muscle hypertrophy without concomitant changes in PA (Reeves et al, 2009; Raj et al, 2012; Baroni et al, 2013b; Fouré et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A second source of inconsistency is the use of reliability estimates of MA parameters that are not comparable between studies [ 16 , 17 , 19 ]. It is also often the case that due to a large number of images, two or more raters determine MA, however the reliability between raters analyzing the same image is scarcely reported [ 20 ]. Furthermore, reliability of US estimates of MA has only been scarcely examined in the older population.…”
Section: Introductionmentioning
confidence: 99%